Insights into Molecular Interaction of Flavonoid Compounds in Citrus Peel Bound to Collagenase and Elastase Enzymes: A Computational Study - Priani, Sani Ega; Fakih, Taufik Muhammad (UI Scholars Hub, 2021)
Citrus peels contain various phytochemical active compounds such as flavonoids that are useful for antiaging cosmetic products. This study was conducted to identify the anti-collagenase and anti-elastase activities of flavonoid compounds in citrus peel and to determine the molecular interaction mechanism using the molecular docking method. The study was carried out through several stages, including preparation of enzyme macromolecules, preparation of flavonoid compound molecules, validation of molecular docking, identification of binding-free energy, visualization of interaction conformations, and predictions of molecular skin toxicity. The result showed that the flavonoid compounds in citrus peel (hesperidin, naringin, nobiletin, and tangeretin) could bind to collagenase and elastase enzymes. Naringin has the highest affinity for the collagenase enzyme with the binding-free energy of −9.52 kcal/mol, while nobiletin has the highest affinity for the elastase enzyme with the binding-free energy of −6.44 kcal/mol. Compared to EGCG (epigallocatechin gallate), the flavonoid compounds have a lower affinity for the collagenase enzyme but a higher affinity for elastase enzymes. Hydrogen bonds and the hydrophobic interactions dominate the interaction between citrus peel’s flavonoids against the enzymes. When applied to the skin, flavonoid compounds are predicted to have no risk of skin toxicity. The flavonoid compounds of citrus peels are expected to have anti-collagenase and anti-elastase activities.